A NEW RECORD OF BARBATULA (TELEOSTEI: NEMACHEILIDAE) SPECIES FROM THE FERGANA VALLEY (Scientific journal of the Fergana State University, 2024)
To date, seven species of stone loaches (Dzihunia sp., Iskandaria kuschakewitschi, Triplophysa daryoae, T. dorsalis, T. elegans, T. ferganaensis va T. strauchii) have been recorded in the inland waters of the Fergana Valley. This article discusses for the first time a species new to the ichthyofauna of the Fergana Valley, belonging to the genus Barbatula from the the Fergana Valley. Species of the Barbatula are very similar to species of the Triplophysa in terms of their body structure and sexual dimorphism but differ from them in having a small distance between the nostrils.